Tribological Study of Nanoparticles Enriched Bio-based Lubricants for Piston Ring-Cylinder Interaction - Gulzar, Mubashir (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis investigates the tribological viability of bio-based base stock to which different nanoparticles were incorporated for engine piston-ring-cylinder-liner interaction. It determines experimentally the effects of lubricating oil conditions (new and engine-aged) on the friction and wear of the materials used for piston rings and cylinder liners. The specific base stock examined was a trimethylolpropane (TMP) ester derived from palm oil, and the nanoparticles were used as additives to obtain tribologically enhanced bio-based lubricants. The overall analysis of the results demonstrated the potential of nanoparticles to improve the tribological behavior of bio-based base stock for piston-ring-cylinder-liner interaction.